2011
DOI: 10.1016/j.ijrobp.2010.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix Metalloproteinase-7 Polymorphism Rs10895304 Is Associated With Increased Recurrence Risk in Patients With Clinically Localized Prostate Cancer

Abstract: Objectives To investigate whether selected high-risk MMP7 single nucleotide polymorphisms influence tumor biology or clinical outcomes in patients with clinical early-stage prostate cancer undergoing prostatectomy. Methods Two hundred twelve human prostate cancer patients treated with radical prostatectomy were included in the study. Median follow-up was approximately 9.8 years. Genotyping was performed using TaqMan™ technology and custom-designed probes. Three single nucleotide polymorphisms within various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several papers have adopted the candidate gene approach, analysing SNPs associated with genes thought to be related with aggressiveness and progression. Amongst the genes reported to be associated with progression in surgical cohorts include the androgen pathway genes [70], encoding ribonuclease L ( RNASEL ) [71], Wnt signalling pathway genes [69], B‐cell lymphoma gene 2 ( Bcl2 ) [72], matrix metalloproteinases ( MMP ) [73] and KLK [74]. Toll like receptors ( TLR ) SNPs have also been associated with progression postprostatectomy [74].…”
Section: Prostatectomymentioning
confidence: 99%
“…Several papers have adopted the candidate gene approach, analysing SNPs associated with genes thought to be related with aggressiveness and progression. Amongst the genes reported to be associated with progression in surgical cohorts include the androgen pathway genes [70], encoding ribonuclease L ( RNASEL ) [71], Wnt signalling pathway genes [69], B‐cell lymphoma gene 2 ( Bcl2 ) [72], matrix metalloproteinases ( MMP ) [73] and KLK [74]. Toll like receptors ( TLR ) SNPs have also been associated with progression postprostatectomy [74].…”
Section: Prostatectomymentioning
confidence: 99%
“…However, others have identified no change in expression in PrCa [ 42 ] or, indeed, a negative correlation with disease [ 52 ], including when examining the levels of the active form of this enzyme [ 29 , 101 ]. For MMP-7, gene polymorphisms may be important in terms of the risk of the disease [ 28 ] and recurrence [ 63 ], while the relative levels of the inhibitors may also influence the impact of MMP-7 on PrCa progression [ 60 ]. An enforced expression of MMP-7 in PrCa cells has been shown to mediate an increased invasion [ 110 ], while a mouse MMP-7 knockout model exhibited reduced tumor-induced osteolysis [ 88 ], indicating the source of this enzyme may not be critical.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, other MMPs appear to be less significantly involved in PrCa. Thus, most studies reported no association between PrCa and MMP-1 in terms of the expression [ 31 , 48 , 52 , 68 , 74 , 83 ], activation [ 29 ] or polymorphism [ 28 , 44 , 60 , 63 , 64 , 68 , 74 , 81 , 88 , 90 , 110 , 155 ]. However, other studies have reported associations between expression and PrCa [ 46 ], including grade/stage [ 105 , 139 ] and metastatic properties, with MMP-1 ablation shown to reduce invasion [ 154 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hirata et al examined six candidate genes including PTEN and P53, but only SNPs in the BCL-2 gene were an independent risk factor for biochemical relapse [74]. A SNP identified as rs10895304 within the MMP7 gene has been reported as predictive of decreased recurrence-free survival [75]. Morote et al tested 703 patients with localized PrCa, who underwent radical prostatectomy, for a panel of 83 SNPs; 35% of those relapsed within 5 years.…”
Section: • • Radical Prostatectomymentioning
confidence: 99%